Desenvolvimento de sistema de análise para valerato de estradiol baseado em polímeros biomiméticos - Staboli, Thalita Maschk [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Abstracts : The development of analytic methods more selective and sensitive is of great importance for a better quality in the determination of chemical species, therefore increasing the reliability of the results. In this way, the optimization of separation/concentration is still necessary. The use of Molecularly Imprinted Polymers - MIPs have demonstrated to be an efficient tool of analysis with a great potential in minimizing limitations of separation/concentration techniques traditionally employed. In general, the MIPs are obtained by polymerization in the presence of a template to be imprinted so that a polymeric skeleton is formed around the future analyte. In the present work, the template used is Estradiol Valerate (EV), compound used in the hormone replacement therapy (HRT) during climacteric. After the polymerization in bulk and in an anaerobic environment using MAA, EGDMA, AIBN, acetonitrile and VE, the obtained MIP was powdered, sifted (<120 μm) and placed in a soxhlet system containing ethanol at 60 °C, in order to remove the imprinted molecule through six successive washes in periods of 24 hours. The water used in the washings was analyzed using HPLC and spectrophotometry UV/Vis. Then, the obtained MIP was dried at room temperature and 150 mg was inset in SPE cartridges in order to evaluate the polymer's efficiency in the analyte pre-concentration and extraction. To do so, 100,0 mL of VE standard solution (2mg L-1) were pre-concentrated at 4,0 mL min-1 and eluted with 10,0 mL ethanol at 1,0 mL min-1, obtaining recoveries of 53%. Additionally, a NIP (non-imprinting polymer) was prepared to compare the obtained results, in which the recovery was 80%. In the same way, studies were conducted using commercial Strata™-X cartridges, obtaining 53% recovery. Since, the results did not reflect that than was expected, in relation with the MIP efficiency in the recovery, a computational ...
Keywords: Quimica analitica